2013
DOI: 10.1038/ncomms2652
|View full text |Cite
|
Sign up to set email alerts
|

Controlled charge trapping by molybdenum disulphide and graphene in ultrathin heterostructured memory devices

Abstract: Atomically thin two-dimensional materials have emerged as promising candidates for flexible and transparent electronic applications. Here we show non-volatile memory devices, based on field-effect transistors with large hysteresis, consisting entirely of stacked two-dimensional materials. Graphene and molybdenum disulphide were employed as both channel and charge-trapping layers, whereas hexagonal boron nitride was used as a tunnel barrier. In these ultrathin heterostructured memory devices, the atomically thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
233
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 631 publications
(257 citation statements)
references
References 43 publications
10
233
1
2
Order By: Relevance
“…In addition, a new type of the memory device was fabricated with graphene (G) as the FET channel, hBN (B) as the tunnel barrier, and MoS 2 (M) as the charge trapping layer (denoted as GBM) [253,254]. This result confirmed that the MoS 2 layer could act as an effective charge-trapping layer.…”
Section: Memory Devicesmentioning
confidence: 64%
See 1 more Smart Citation
“…In addition, a new type of the memory device was fabricated with graphene (G) as the FET channel, hBN (B) as the tunnel barrier, and MoS 2 (M) as the charge trapping layer (denoted as GBM) [253,254]. This result confirmed that the MoS 2 layer could act as an effective charge-trapping layer.…”
Section: Memory Devicesmentioning
confidence: 64%
“…When a thicker MoS 2 layer and thinner hBN were employed, unipolar conductance and greater hysteresis were observed due to effective electron tunneling and electric-field screening. In addition, the reversed stacking structure (MBG) was also investigated, with a high on/off current ratio and a large memory window [253]. Due to the time-dependent PL, the MoS 2 -graphene heterostructure can also function as a rewritable optoelectronic switch or memory, where the persistent state shows almost no relaxation or decay within experimental timescales, indicating near-perfect charge retention [255].…”
Section: Memory Devicesmentioning
confidence: 99%
“…As the family of 2D materials is increasing gradually in recent years, this kind of heterostructures allows a greater freedom and a far greater number of combinations than any traditional growth method. Furthermore, van der Waals heterostructures have already led to the observation of numerous exciting physical phenomena and novel applications such as correlated light emitters [28][29][30][31], ultra-high speed photodetectors [32,33], new generation field effect transistors [34][35][36][37], and memory devices [38][39][40][41] compared to their individuals. Therefore, the investigation of van der Waals heterostructures shows great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Molybdenum disulfide (MoS 2 ) has been one such extensively studied and revisited material since its first report by Joesen et al in 1986 [5][6][7][8]. After the successful demonstration of MoS 2 -based field-effect transistors, and following many other interesting electronic and optoelectronic applications [9][10][11], various methods have evolved for the synthesis of good-quality MoS 2 atomic layers. Liquid exfoliation of bulk crystals for getting atomic thin layers can be successfully optimized to produce large amounts of layered materials [12,13].…”
Section: Introductionmentioning
confidence: 99%